Report on proposed new interior design of Hugo Boss retail for Melium Sdn Bhd at The Curve,No.6 Jalan PJU 7/3, Mutiara Damansara, 47810 Petaling Jaya, Selangor Darul Ehsan / Muhammad Abdul Halim Che Ali - Che Ali, Muhammad Abdul Halim (Faculty of Architecture, Planning and Surveying, 2010)
The final project for the student of Diploma in Interior Design is a just such an education towards the student’s knowledge about the whole aspect on interior design that had been learned from basic technical to the final presentation of the proposed design. The project that had been chosen for the final project is to propose a New Interior Design of Hugo Boss retail for Melium Sdn. Bhd at the Curve.No.6 Jalan PJU 7/3, Mutiara Damansara, 47810 Petaling Jaya,Selangor Darul Ehsan.This proposed retails to the customers to come and buying Hugo Boss products at retail and mostly the product of Hugo Boss are exclusive product. The product includes clothes, accessories,coat and many more. The target market are citizen around Selangor and also tourist especially who come from oversea. Beside that target market also can be any corporate company to buy any kind of Hugo Boss product. The concept and image that had been chosen not only must be suitable with the products, but it must have a strong identity of Hugo Boss so customer will familiar of Hugo Boss design, where it will give a strong character to the retails. Connected to that, the chosen design style for Hugo Boss is based on modem design, which goes all the way with the client’s needs as they want their retail to have the modem design look and at the same time would attract the customers to enter inside the retail. Before getting a desired design that is suitable with the client’s needs, some data analysis has been done. The research included on types of customers that usually comes to Hugo Boss retail, types of services, type of products or brand often buy from customer, spaces to be included in the proposed area as the proposed retail shop. Other information of the study is through interviews, printed media, internet, observation, and through the result from the case studies either locally or internationally.